Buah Naga (Hylocereus polyrhizus) Meningkatkan Kadar Hemoglobin pada Remaja Putri - Thamrin, Halida; Budu, Budu; Nontji, Werna; Sharief, Suchi Avnalurini (Window of Health : Jurnal Kesehatan, 2018)
Young women have a high risk of anemia, this is due to iron loss during menstruation. Female teenagers have an increased risk of anemia compared to young men because young women experience menstruation every month and the desire to reduce food so that the body lacks important nutrients such as iron. This study aims to determine the effect of dragon fruit (Hylocereus polyrhizus) on increasing hemoglobin levels in young women. This study used an experimental design with pretest-posttes with control group design. The sample in this research is student Prodi DIII Kebidanan. The total sample of 32 female students was divided into 2 groups, 16 female students were given dragon fruit (Hylocereus polyrhizus) as intervention group and 16 female students who were given nutrition education as control group. Measurements of hemoglobin levels were performed before and after treatment for 8 weeks, periodic measurements were performed every 2 weeks. Data analysis using Paired t-test. The results showed no effect but no significant difference of dragon fruit (Hylocereus polyrhizus) to increase hemoglobin level in female adolescent (P> 0,05).